2014
DOI: 10.3147/jsfp.49.121
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Serological Characterization of a Non-gliding Strain of Tenacibaculum maritimum Isolated from a Diseased Puffer Fish Takifugu rubripes

Abstract: T h e g e n u s T e n a c i b a c u l u m b e l o n g s t o t h e f a mi l y F l a v o b a c t e r i a c e a e , p h y l u m Ba c t e r o i d e t e s , a n d T . ma r i t imu m ( S u z u k i e t a l ., 2 0 0 1 ) i s a n e x c l u s i v e l y ma r i n e s p ec i e s ( Be r n a r d e t e t a l . , 1 9 9 6 ) . I t i s a Gr a m-n e g a t i v e , g l i d i n g b a c t e r i u m a n d c a u s e s t e n a c i b a c u l o s i s , a n u l c e r at i v e d i s e a s e o f ma r i n e f i s h . T h e d i s e a s e wa s f … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
2
16
1
1
Order By: Relevance
“…Differences in virulence between the isolates were observed. A variation in virulence among T. maritimum strains has also been shown in other studies (Avendaño-Herrera et al, 2006a;Rahman, Suga, Kanai, & Sugihara, 2014;van Gelderen et al, 2010). Interestingly, these differences seem to be evident within Western Canadian genotypic strains.…”
Section: Discussionsupporting
confidence: 79%
“…Differences in virulence between the isolates were observed. A variation in virulence among T. maritimum strains has also been shown in other studies (Avendaño-Herrera et al, 2006a;Rahman, Suga, Kanai, & Sugihara, 2014;van Gelderen et al, 2010). Interestingly, these differences seem to be evident within Western Canadian genotypic strains.…”
Section: Discussionsupporting
confidence: 79%
“…In vitro analyses demonstrated that T. maritimum is able to degrade chondroitin sulfate A and C on marine agar 2216, as showed by the formation of a degradation halo around the bacterial growth ( Figure 3A ). Although a chondroitin C-lyase activity was recently suggested for T. maritimum ( Rahman et al, 2014 ), our results demonstrate the ability of this bacterium to also degrade chondroitin sulfate A. Other phylogenetically close Tenacibaculum species, such as T. discolor , T. jejuense , or T. soleae do not display this chondroitin AC lyase activity under the same conditions.…”
Section: Resultscontrasting
confidence: 68%
“…Tenacibaculum maritimum (formerly Flexibacter maritimus ), a member of the family Flavobacteriaceae, phylum Bacteroidetes ( Suzuki et al, 2001 ), is the etiological agent of tenacibaculosis, a very serious bacterial disease of many commercial marine fish species (for a review, see Avendaño-Herrera et al, 2006b ), responsible for considerable economic losses in all major areas of marine finfish aquaculture worldwide (i.e., Japan, Europe including the Atlantic, Channel and Mediterranean coasts, North America, Australia, and the Red Sea). Moreover, T. maritimum can affect a large number of feral, captive, and cultured fish species such as: Dover sole ( Solea solea ), Senegalese sole ( Solea senegalensis ), wedge sole ( Dicologoglossa cuneata ), turbot ( Scophthalmus maximus ), Atlantic salmon ( Salmo salar ), Japanese flounder ( Paralichthys olivaceus ), yellowtail ( Seriola quinqueradiata ), red sea bream ( Pagrus major ), black sea bream ( Acanthopagrus schlegelii ), gilthead sea bream ( Sparus aurata ), European sea bass ( Dicentrarchus labrax ), puffer fish ( Takifugu rubripes ), Pacific sardine ( Sardinops sagax ), lumpsucker ( Cyclopterus lumpus ), and sand tiger shark ( Carcharias taurus ) ( Bernardet et al, 1990 ; Avendaño-Herrera et al, 2006a ; López et al, 2009 ; AbdEl-Galil and Hashiem, 2011 ; Rahman et al, 2014 ; Florio et al, 2016 ; Småge et al, 2016 ; and references therein]. Affected fish usually display a variety of external signs including eroded mouth, skin ulcers, fin necrosis, and tail-rot.…”
Section: Introductionmentioning
confidence: 99%
“…Variation in pathogenicity between T . maritimum strains has been shown in other studies, including other fish species [ 2 , 35 , 36 ]. Differences in pathogenicity also occur between isolates belonging to the same multilocus sequence type (genetically identical on 11 housekeeping gene sequences) as was the case for TmarCan16-1 and TmarCan16-2 [ 11 ].…”
Section: Discussionsupporting
confidence: 68%